2020
DOI: 10.1002/rcs.2112
|View full text |Cite
|
Sign up to set email alerts
|

Robotic sphincter saving rectal cancer surgery: A learning curve analysis

Abstract: BackgroundLonger operation time is one of the major obstacles in front of the proposed benefits of robotic rectal surgery. We intended to evaluate the learning process for robotic surgery in sphincter saving rectal cancer surgery.MethodsThe learning curve was evaluated using the cumulative sum (CUSUM) method. The variable evaluated for learning curve calculation was the operative time.ResultsThe learning curve was divided into two phases: initial 52 operations comprised phase 1 and the following 44 operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…We observed an accelerated learning curve for robotic surgery, with the surgeon achieving proficiency after just 17 cases. Similarly, previous studies have found that the learning curve for rectal cancer surgery with the da Vinci robot was 15–50 cases [ 16 18 ]. The accelerated learning curve for RTME can be explained as follows.…”
Section: Discussionsupporting
confidence: 92%
“…We observed an accelerated learning curve for robotic surgery, with the surgeon achieving proficiency after just 17 cases. Similarly, previous studies have found that the learning curve for rectal cancer surgery with the da Vinci robot was 15–50 cases [ 16 18 ]. The accelerated learning curve for RTME can be explained as follows.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies’ primary aim was to define the learning curve, though for nine studies it was a secondary aim [ 26 , 27 , 29 31 , 42 , 43 , 46 , 59 ]. Thirteen studies reported on institutional learning curves [ 8 , 9 , 11 , 13 , 31 33 , 39 , 41 – 43 , 49 , 59 ], while the others reported on surgeons’ individual learning curves. Previous experience with colorectal surgery was mentioned in twenty-one studies [ 8 10 , 13 , 15 , 24 , 25 , 28 , 29 , 31 , 35 , 37 , 39 42 , 45 47 , 51 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies scored high on all criteria of the MINORS tool. Nineteen out of 41 non-comparative studies adequately reported more than half of the required criteria [ 9 12 , 15 , 24 , 25 , 27 , 33 , 35 , 37 , 38 , 48 50 , 53 , 55 ]. Study quality was highest among the TaTME studies, and varied most among the R-TME and L-TME studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations